(untitled) (International Conference on Computers in Education, 2019)
Code reading is a prerequisite of program comprehension which is a fundamental task in software development. Strategies employed on code reading affect the programmer’s success rate of understanding tasks such as debugging. However, there is still limited knowledge about the code reading strategies used by students while performing bug finding task. In this paper, the author describes a summary of her research on novice programmer debugging skills using eye tracking data as a methodology. Eye tracking data were extracted and analyzed using visual effort metrics and sequential analysis of scanpaths using a clustering algorithm to determine common code reading patterns. The author’s research findings revealed differences on the code reading patterns and code reading strategies of high and low performing students. Empirical evaluation on the effectiveness of the strategies used by high performing students was also conducted which suggests that by teaching these strategies to students, improved debugging performance can be observed.